THE IMPACT OF GOVERNMENT SPENDING ON THE UNEMPLOYMENT RATE IN IRAQ FOR THE PERIOD 2004 – 2022 - Professor Muneam Ahmed Khudhair; Lecturer. Khalil Refaat Abdulah (Scholar Express Journals, 2025)
The study aimed to analyze the phenomenon of unemployment in Iraq and to identify the impact of government spending on it, as well as to evaluate the effectiveness of fiscal policy in Iraq using the government spending tool and the extent of its contribution to reducing unemployment rates for the period 2004-2022. The study also assumed a positive impact of government spending on the unemployment rate in Iraq. The results showed an inverse and significant effect in the short and long term between government spending and the unemployment rate. The interpretation coefficient showed that 95% of the changes in the unemployment rate were due to changes in government spending. In addition, there was no problem of autocorrelation, and no problem of homogeneity of variance at a significance level of 5%. The study recommended that achieving economic growth is indispensable for achieving sustainable development and eliminating unemployment and poverty in Iraq. This cannot be achieved without growth in the private sector as a basic and primary tool for economic growth, generating job opportunities, and removing all obstacles that stand in its way. It also stressed the need to focus on small and medium enterprises, which would employ the largest possible number of unemployed people. Furthermore, increasing investments in Iraq would help solve the unemployment problem, which could increase job opportunities. Creating jobs is a priority that should not be overlooked. In order to expand opportunities, it is necessary to create a climate in which the private sector and foreign investments can contribute to eliminating this phenomenon and providing job opportunities for Iraqis according to their academic qualifications, and to establish an incentive system that contributes to attracting investors .
Keywords: government spending; unemployment